They don’t represent us - Urtzi Grau; Cristina Goberna (Materia Arquitectura, 2014)
The wave of urban protests characterized by the occupation of public space that has proliferated globally since 2010 has, as a common link, the questioning of representation models. Architecture, traditionally responsible for institutional representation to the citizens, is not only part of the controversy but it also defines protest methods. Reviewing the 15-M and Occupy Wall Street files, the article researches the demands on the practice of architecture implicit in these manifestations.